Implemetation of The Simple Additive Weight (SAW) Method for Recommendations for City Survey On Company Projects - Julio Warmansyah; Agus Susanto (Sekolah Tinggi Ilmu Komputer Binaniaga, 2022)
DEKA has multiple expertise in the market research industry by conducting various types of research through qualitative and quantitative methods to generate valuable and actionable insights, guiding clients in the process of reviewing, learning, and developing strategic marketing plans, as well as customer-oriented organizational transformation. Deka also provides data-driven strategies and recommendations, taking into account the key purchase drivers for customer acquisition, brand revitalization, product/service, innovation, price optimization, and marketing communication strategies.Â To obtain quality data, it must also be carried out in an appropriate manner starting from project preparation by compiling a Job summary, conducting kick-off meetings both externally and internally, preparing the team in the field, compiling a budget plan, consolidating with the teams involved through briefings and making the implementation guidelines and the timeline